A Guide to Planning Cyclelogistics Hubs. - (:unkn) unknown (My University, 2021)
This guide equips readers with a newfound inspiration for moving cities towards cyclelogistics cargo bike hubs. Though there’s nothing particularly new about cargo bikes, the world has seen a growing trend in using them for a plethora of different purposes, one of these being for deliveries around cities. Their relative ease, affordability, and accessibility make them an increasingly popular choice for CEP services in big and small cities. With the help of research from the University of Magdeburg, this guide details the steps that can be taken to develop cyclelogistics hubs, and what each stage of planning looks like.
Keywords: Fahrradnutzung; Lastentransport; Zulieferindustrie; Stadtlogistik; Nachhaltige Mobilität; Lastenfahrrad